التفكير الأخلاقي و علاقته بالمسؤولية الاجتماعية لدى عينة من تلاميذ التعليم الثانوي - عون, علي; شطة, عبدالحميد; رابحي, عبدالمالك (جامعة الوادي - University of Eloued, 2017)
هدفت هذه الدراسة إلى الكشف عن العلاقة بين التفكير الأخلاقي و المسؤولية الإجتماعية لدى تلاميذ التعليم الثانوي، وذلك من خلال معرفة واقع كل من التفكير الأخلاقي و المسؤولية الإجتماعية بكل من ثانويات مدينة الأغواط، كما تسعى إلى معرفة الفروق في مستوى التفكير الأخلاقي تعزى لمتغير الجنس )ذكر- أنثى(، والتخصص) علمي- أدبي). وتكونت عينة الدراسة من 60 تلميذا من السنة الثالثة ثانوي، كما اعتمدنا في دراستنا على مقياسين، الأول خاص بالتفكير الأخلاقي من إعداد " فوقية عبد الفتاح " (2001)، أما الاستبيان الثاني فهو خاص بالمسؤولية الإجتماعية من إعداد "مشرف ميسون" (2009) ، واعتمدنا على المنهج الوصفي لملائمته لموضوع دراستنا، وتم استخدام الأساليب الإحصائية التالية: النسبة المئوية، المتوسط الحسابي ،اختبار″ ت″، وأشارت نتائج الدراسة إلى وجود علاقة ارتباطية موجبة دالة بين مستوى التفكير الأخلاقي والمسئولية الاجتماعية لدى تلاميذ التعليم الثانوي بالأغواط ، كما كشفت النتائج عن وجود فروق ذات دلالة في مستوى التفكير الأخلاقي بين الذكور والإناث ولصالح الإناث ، في حين لا توجد فروق ذات دلالة في مستوى التفكير الأخلاقي لدى طلبة الجامعة تعزى لمتغير التخصص This study aimed to reveal the relationship between moral thinking and social responsibility among students in secondary education, through knowledge of the reality of each of moral thinking and social responsibility in all of the high schools Laghouat City, also seeks to know the differences in the level of moral thinking due to the variable sex( Male – Female) and specialization, (scientific, literary). The study sample consisted of 60 students of the third year of secondary, as we have adopted in our study on the two measures, the first special moral thinking of preparation "instant Abdel-Fattah" (2001), while the second questionnaire is the social responsibility of preparing "Musharraf Mason " (2009), and we relied on the descriptive approach for suitability to the subject of our study, were used the following statistical methods: Percentage, arithmetic average, the test "T", and study results indicated the presence of correlation is positive function between the level of moral thinking and social responsibility among students in secondary education Laghouat, as findings revealed There are significant at the level of moral thinking between male and female differences in favor of females, while there were no significant differences in the level of moral thinking among university students due to the variable level of academic specialization differences.
دراسة ميدانية ببعض ثانويات بلدية الأغواط
مقال في مجلة السراج في التربية وقضايا المجتمع بجامعة الوادي
Keywords: التفكير الأخلاقي ، المسؤولية الإجتماعية. التعليم الثانوي; . moral thinking, social responsibility